Operational Management of Repair Container to Minimize Goods Damage During the Shipping ProcessOperational Management of Container Repairs to Minimize Goods Damage During the Shipping Process - Pradita, Ristania Lorensa Enggar; Fauziah, Luluk (Asian Journal of Logistics Management, 2023)
One of the services provided by the container depot is maintenance and repair (M&R) with a function to repair damaged containers during the process of shipping goods. The purpose of this study is to determine the existing management activities in an empty container depot, especially in maintenance and repair operational activities. The research method used in the study conducted is a qualitative method with observation, interview with informan, literature studies, documentation, and triangulation. The results of this research is, the operational management activities of repair containers at the PT. Sricon Logistik Indonesia Semarang has been running quite well, but it is necessary to make a standard of documentation police in survey activity and the accuracy of loading and unloading activities at TPKS and improve the skills of the company's human resources.